Gender and Modern Supply Chains in Developing Countries - Miet Maertens; Johan F. M. Swinnen (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2009)
The rapid spread of modern supply chains in developing countries is profoundly changing the way food is produced and traded. In this paper we examine the gender implications in modern supply chains. We conceptualize the various mechanisms through which women are directly affected, we review existing empirical evidence and add new survey-based evidence. Empirical findings from our own survey suggest that modern supply chains may be associated with reduced gender inequalities in rural areas. We find that women benefit more and more directly from large-scale estate production and agro-industrial processing, and the creation of employment in these modern agro-industries than from smallholder contract-firming.
Keywords: O12; Q17; J16; J43; 330; gender; modern supply chains; vertical coordination; poverty